Effect of vitamin e and selenium supplementation on the antioxidant content of milk and dairy products in dairy cows - Sütő, Berta Vanda; Kárnyácki, Zsuzsanna; Béri, Béla (Acta Agraria Debreceniensis, 2011)
In 2007, the aim of the Ányos Jedlik program and the call for tenders was to support application-oriented, strategic research and development projects, which can increase the competitiveness of the Hungarian economy. In the framework of our project, we intended to examine whether non-protected antioxidants - in this case: vitamin E and selenium – used as feed-additives can increase the antioxidant content of milk. The milk with an increased level of vitamin E and selenium content can be used for producing functional foods which will represent competitive products on the current market of milk products. Our results show that the use of vitamin E and selenium as feedadditives can significantly increase the amount of vitamin E and selenium in the milk and also in the diary products.